Atheroprotective role of high-density lipoprotein (HDL)-associated sphingosine-1-phosphate (S1P). (1st June 2014) - Potì, Francesco; Simoni, Manuela; Nofer, Jerzy-Roch
Abstract: Numerous epidemiological studies documented an inverse relationship between plasma high-density lipoprotein (HDL) cholesterol levels and the extent of atherosclerotic disease. However, clinical interventions targeting HDL cholesterol failed to show clinical benefits with respect to cardiovascular risk reduction, suggesting that HDL components distinct from cholesterol may account for anti-atherogenic effects attributed to this lipoprotein. Sphingosine-1-phosphate (S1P)—a lysosphingolipid exerting its biological activity via binding to specific G protein-coupled receptors and regulating a wide array of biological responses in a variety of different organs and tissues including the cardiovascular system—has been identified as an integral constituent of HDL particles. In the present review, we discuss current evidence from epidemiological studies, experimental approaches in vitro, and animal models of atherosclerosis, suggesting that S1P contributes to atheroprotective effects exerted by HDL particles.